2000
DOI: 10.1017/s0266467400001723
|View full text |Cite
|
Sign up to set email alerts
|

Long-term permanent plot observations of vegetation dynamics in Budongo, a Ugandan rain forest

Abstract: Species composition and turnover that have occurred in a series of permanent sample plots established during the 1930s and 1940s in Budongo, a semi-deciduous Ugandan forest, are reported. The plots were established as part of a sequence first used to describe forest succession, five of which have been maintained and which were last measured in 1992-1993. One plot (plot 7) provides 53 y of data from old-growth pristine forest. Plot 15 was established in wooded grassland at the forest edge and is now closed high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
147
1
37

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(187 citation statements)
references
References 54 publications
2
147
1
37
Order By: Relevance
“…In our sites at a decadal interval two species (Jatropha gossypifolia and Streblus asper) were newly recorded in sites MM and AP respectively. Sheil et al (2000) also reported increased species richness over a time period in Budongo rain forest, Uganda. In the present study the Shannon diversity index increased in all the sites, while the Simpson in- Table 4.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In our sites at a decadal interval two species (Jatropha gossypifolia and Streblus asper) were newly recorded in sites MM and AP respectively. Sheil et al (2000) also reported increased species richness over a time period in Budongo rain forest, Uganda. In the present study the Shannon diversity index increased in all the sites, while the Simpson in- Table 4.…”
Section: Discussionmentioning
confidence: 83%
“…Monitoring can also aid in collecting reliable scientific information on habitat composition, structure and dynamics and in evaluating existing management approaches and their impacts on forest ecosystems (Baithalu et al 2013). Long-term studies of tree population dynamics are critical for understanding the conservation need of tropical forest ecosystems (Hubbell and Foster 1990;Condit 1995;Sheil et al 2000). Several longterm studies of tree population dynamics are available in both tropical and temperate forests (Lieberman and Lieberman 1987;Kochummen and Manokaran 1987;Foster and Hubbell 1992;Sukumar et al 1992;Balslev and Korning 1994;Bhat et al 2000;Lwanga et al 2000;Battles et al 2003;Takahashi et al 2003;Fashing et al 2004;Kariuki et al 2006;Baithalu et al 2012Baithalu et al , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…1C e 1D) contrariou, pelo menos em parte, a teoria de que em fl orestas tropicais preservadas a mortalidade é normalmente balanceada pelo recrutamento (Richards 1996;Rolim et al 1999). Por outro lado, Manokaran & Kochummen (1987), Felfi li (1995a) e Sheil et al (2000) observaram que períodos de instabilidade ou desbalanceamento entre mortalidade e recrutamento podem fazer parte dos ciclos rítmicos de algumas fl orestas não perturbadas, que alcançam um balanço por meio de períodos com elevada mortalidade ou perda de biomassa, alternados com períodos de elevado recrutamento ou ganho de biomassa. Nestes casos, o desbalanceamento entre mortalidade e recrutamento é atribuído ao processo natural, uma vez que a mortalidade ocorre primeiro, sendo sucedida pelo recrutamento (Felfi li 1995b;Pinto 2002).…”
Section: Número De Indivíduos E áRea Basalunclassified
“…Nesse sentido, após o período de elevada mortalidade constatado no presente estudo, a queda das árvores mortas ocasionará a abertura de novas clareiras, fornecendo condições favoráveis para o recrutamento de novos indivíduos e iniciando uma nova fase do ciclo fl orestal rítmico, tal como observado por Felfi li (1995b) e Pinto (2002). Segundo Sheil et al (2000), nestes casos a queda de árvores, em função da elevada mortalidade, pode constituir o principal fator modulador do processo de dinâmica fl orestal em curtos períodos, ocasionando perdas imediatas e consideráveis de biomassa, acompanhadas de redução da densidade de indivíduos.…”
Section: Mortalidade E Recrutamentounclassified
“…APPOLINÁRIO et al, 2005;DAMASCENO-JUNIOR et al, 2004) não são comuns no centro-sul do Brasil. Esses estudos são importantes, pois permitem o monitoramento e a previsão dos processos de transformação de populações e comunidades vegetais pós-distúrbio natural ou antrópico (SHEIL et al, 2000;GOMES et al, 2004).…”
Section: Introductionunclassified